Pengaruh Latihan Sirkuit Training terhadap Kecepatan Lari 100 Meter pada Ekstrakurikuler Atletik - Ni Kadek Rani Puspa Nirmala Sari; I Ketut Iwan Swadesi; Luh Putu Tuti Ariani (Jurnal Sporta Saintika, 2025)
Speed is a crucial component in athletics, particularly in the 100-meter sprint event. To improve running speed, effective and varied training methods are required, one of which is circuit training. The study aims to examine the effect of circuit training on improving 100-meter sprint speed among athletics extracurricular students at SMA Negeri 2 Tabanan. The research employed a quasi-experimental design with a One-Group Pretest and Posttest approach. The sample consisted of 25 students participating in circuit training for six weeks, with three sessions per week and each session lasting 60 minutes. Sprint speed was measured before and after the training using a digital stopwatch. Data were analyzed using SPSS with a paired sample t-test after conducting the Shapiro-Wilk normality test. The results showed a significant decrease in 100-meter sprint time in the posttest compared to the pretest (p = 0.000 < 0.05), with an average time difference of 0.36720 seconds. These findings indicate that circuit training effectively improves 100-meter sprint speed in extracurricular athletics students. This study recommends integrating circuit training into the training program to optimally enhance athletic performance.